Clinical Assessment and Prognostic Evaluation of Tumor Markers in Patients with Gastric Cancer. Issue 2 (April 2013) - Jiexian, Jing; Xiaoqin, Xu; Lili, Du; Baoguo, Tian; Ting, Sun; Xianwen, Zhao; Cunzhi, Han
Aim: To investigate the relationship between the serum levels of CEA, CA19-9, CA24-2, CA72-4, and AFP in patients with gastric cancer (GC) and their clinicopathological characteristics; to analyze the efficacy of these tumor markers in evaluating the prognosis of GC. Methods: Overall, 389 patients with GC either located in the gastric cardia (132), the pyloric antrum (112) or the body of the stomach (145) were included in the study. Serum levels of CEA, CA19-9, CA72-4, and AFP were detected with the ECLIA method, while CA24-2 was measured with ELISA. Results: First, the serum level of CEA in GC patients with a cardia-located cancer was significantly higher than in patients with pyloric antrum-located cancer (p=0.050). CA72-4 level in patients with GC located in the gastric body was significantly higher than in patients with cardia and pyloric antrum-located cancers (p=0.042 and p=0.039, respectively). Secondly, serum CA19-9 and CA24-2 levels in females with cardia-located GC were significantly higher than those in males with the same type of tumor (p=0.037 and p=0.033, respectively). Additionally, for females with gastric body-located GC the levels of CEA and CA72-4 were significantly higher than those in male patients with the same type of tumor (p=0.047 and p=0.048, respectively). Conversely, in female GC patients with pyloric antrum-located cancer the serum levels of CA19-9 and CA24-2 were significantly lower than those in male patients with the same type of cancer (p=0.013 and p=0.007, respectively). Moreover, CEA, CA19-9, CA24-2, and CA72-4 levels were strongly related to TNM grade and histological anatomy stage, whereas CEA and CA72-4 levels were strongly related to lymph node stage (p=0.000 and p=0.042, respectively). Patients with vascular embolism had higher serum levels of CEA, CA19-9, CA24-2, and CA72-4 compared with patients without vascular embolism (p=0.005, p=0.031, p=0.007, and p=0.014, respectively). In patients with distant metastases and ascites the levels of CEA, CA19-9, and CA24-2 were higher than in patients without these conditions (p=0.003, p=0.001, p=0.001, p=0.016, p= 0.011, and p=0.030, respectively). Serum CEA, CA19-9, and CA24-2 levels showed correlations with tumor invasive depth and growth types (p=0.001, p=0.040, and p=0.035, respectively). Patients with lump and catheter tumor growth types had significantly higher AFP levels than patients with invasion and anabrosis growth types (p=0.034 and p=0.005, respectively). Tumor size was correlated with the preoperative serum levels of CEA, AFP, and CA72-4 (p=0.007, p=0.020, and p=0.008, respectively). Additionally multiple linear regression analysis showed that preoperative levels of CEA and CA72-4 were correlated to TNM stages, CA19-9 and CA24-2 levels were correlated to both gender and distant metastasis, and AFP was correlated only to ascites. During follow-up there were 115 deaths. Median survival time for GC patients with negative preoperative CEA was 18.07 months, and was 10.97 months for patients with preoperative CEA positive levels (p=0.0005). Similarly, the median survival time for GC patients with negative preoperative CA72-4 was 33.60, and was 16.03 months for patients with preoperative CA72-4 positive levels (p=0.0041). Conclusions: The preoperative levels of CEA, CA19-9, CA24-2, CA72-4, and AFP were closely related to TNM grade, gender, distant metastasis and ascites. These makers seem to play important roles in predicting recurrence and metastasis, and in evaluating prognosis.